Risk factors for mortality in fungal infections - (:unkn) unknown (Turkiye Klinikleri, 2009)
Objective: This study aimed to investigate the frequency of fungal in fections in our intensive care unit (ICU) and the risk factors directly associated with mortality. Material and Methods: The data of 625 patients ad mitted to the Medical ICU between 2003 and 2006 were reviewed retrospectively. Results: The percentage of patients with at least once fungal isolation was 11% (n= 73). Fungal species were isolated from blood samples (n= 35), urine (n= 28), deep tracheal aspirate (DTA, n= 40) and catheters (n= 14). The association between the localization of fungal infection and mortality was examined and a significant correlation between fungemia and mortality was found (p= 0.002); however, the correlation between mortality and fungal isolation from urine, DTA and catheters was not significant (p> 0.05). Multivariate logistic regression analysis to detect the factors for mortality in patients with isolated fungal species revealed that mortality was 5.2 times more frequent among fungemic patients in comparison to other groups (confidence interval: 1.11-25 p=0.036). Conclusion: In ICU patients, fungemia itself had a direct correlation with mortality. The goal of treatment should be the early detection of fungemia and reducing mortality with the initiation of the therapy as early as possible. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Fungemia; Hospital mortality; Risk factors